Mothers Practices and Factors Affecting Sunlight Exposure of Their Infants in Adami Tulu Jido Kombolcha District, East Shoa Zone, Oromia Region, Ethiopia, 2022: A Community Based Cross-Sectional Study - Abdulhakim Hora Hedato MPH; Abdissa Alemu Dibaba MPH; Ephrem Lejore Sibamo MPH; Wondwosen T/Silasie Kidane MSc; Beriso Furo Wengoro PhD; Fikiru Yigezu Jaleta MSc; Abdulkerim Hassen Moloro MSc (SAGE Publishing, 2024)
Background. Vitamin D deficiency (VDD) is a global health concern affecting people of all ages. The Ethiopian guidelines recommend sun exposure for neonates starting from 2 weeks old, with 15 to 20 minutes per day. However, evidence suggests that the implementation of this recommendation is inconsistent. Most studies conducted in Ethiopia regarding infant sunlight exposure have been limited to health facilities and towns. Objective. this study aimed to assess mothers' practice, and factors affecting the sunlight exposure of their infants in Adami Tulu Jido Kombolcha district, East Shoa Zone, Oromia Region, Ethiopia, 2022. Method. A community based cross-sectional study design was conducted among 575 mothers with their infant's from March 11 to 25, 2022. A lottery method sampling technique was employed to select local administrative units and systematic random sampling employed to select study participants. Practices and knowledge were assessed by categorizing mothers based on their responses to practice and knowledge questions, respectively. Mothers who scored above the mean value of 4.5 were classified as having good practice, while those who scored 6.9 or below on the knowledge questions were classified as having poor knowledge. Data were collected through face-to-face interviews using both semi-structured and structured questionnaires. The data were then entered into EPI Data version 3.1 and exported to SPSS version 25 for analysis. The association between variables was analyzed using bivariate and multivariable binary logistic regression and level of significant determined with adjusted odd ratio at 95% CI and P -value less than <.05. Result. All 575 mothers were interviewed and responded 100%. Out of 567 mothers, 55.2% had good practice of infant sunlight exposure. Lack of advice at health facility (AOR = 3.05, 95% CI: 1.08, 8.60), absence of postnatal care follow up (AOR = 2.38, 95% CI: 1.15, 4.94) and poor knowledge about sunlight exposure (AOR = 1.70, 95% CI: 1.15, 2.50) were factors associated with practice of infant sunlight exposure. Conclusions. In this study, more than half of the mothers had good practice of infants' sunlight exposure. This study highlights the importance of improving maternal knowledge and healthcare practices related to infant sunlight exposure. Key factors affecting these practices include lack of advice at health facilities, absence of postnatal care follow-up, and poor maternal knowledge. To address these issues, healthcare providers, local health offices, and mass media should focus on educational programs and strengthening advice during health visits. Future research should use validated tools and mixed-method approaches to better understand the social and cultural factors at play. Establishing national guidelines and studying infant serum vitamin D levels can further enhance community awareness and promote the benefits of sunlight exposure.